Low-Grade Mucoepidermoid Carcinoma: Rare Pulmonary Tumor with Excellent Prognosis - Rupali Bavikar; Saloni Bharadwaj; Yamini Ingale; Charusheela Gore; Saurabh Patil (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Mucoepidermoid carcinoma (MEC) of the lung is a rare form of lung cancer that is classified into low grade and high grade based on histological features. Surgical resection is the primary treatment for low-grade MEC with excellent outcomes, while high-grade MEC is a more aggressive form of malignancy. We report a case of a 43-year-old woman who presented with dyspnea on exertion and chest pain. Imaging studies revealed a mass involving the right lower lobe of the bronchus. Bronchoscopy, surgical resection, and pathological examination revealed a low-grade MEC with tumor-free margins. MEC is a rare type of lung cancer, with only a few reported cases. This patient illustrates a typical presentation for low-grade MEC, wherein surgical resection is considered curative. MEC of the lung is a comparatively rare low-grade tumor that reportedly carries a good prognosis. However, one should consider the possibility of high-grade MEC.